Impact of meteorological and processing factors on metabolite composition of Darjeeling tea - Dwaipee De; Sreerupa Sarkar; Himashree Chhetri; Jhelam Chatterjee; Nitu Sinha; Sujit Das; Abhijit Sarkar; Susmita Das; Sonali Ray (Journal of Analytical Science and Technology)
Abstract Meteorological and edaphic factors significantly affect the first flush metabolite composition of Darjeeling tea, impacting flavor, nutrition, and customer preferences. The Camellia sinensis var. sinensis grown in the Darjeeling hills was sampled at different stages of processing. 75 metabolites were identified using a GC/MS-based metabolomic and chemometric technique. The study aimed to pinpoint quality markers and create a database for Darjeeling tea authenticity, India’s first geographical indication product. Principal component analysis and partial least squares discriminant analysis revealed changes in tea metabolites during processing, while the chemometric study demonstrated variations in key compounds. Antioxidant activity exhibited significant variations among the samples with final processed showing highest antioxidant potential. The concentration of amino acids increased significantly (p < 0.05) from fresh tea leaves to the final processed product. Conversely, the content of organic acids, inorganic acids, and fatty acids was observed to decrease. Additionally, caffeic acids, epicatechin, epigallocatechin, chlorogenic acid, 3, 4-dihydroxybenzoic acid, and 4-hydroxycinnamic acid increased in concentration, while catechin, (-)-epicatechin, gallic acid, pyrogallol, quinic acid, shikimic acid, and arbutin decreased significantly in concentration in the final processed tea. Meteorological parameters were documented during the study period, showing variation in the levels of PM2.5, PM10, O3, NO2, and SO2. The findings of this study offer insightful information on the variables influencing Darjeeling tea metabolite composition, which tea producers and processors can use to raise the standard and authenticity of this beverage. Graphical abstract